Assessment for cardiovascular fitness in patients with stroke: which cardiopulmonary exercise testing method is better?. Issue 5 (4th July 2022) - Mustafa, Esra; Aytür, Yesim Kurtais
ABSTRACT: Background: Assessment for cardiovascular disease (CVD) is important in stroke patients, both being one of the main factors limiting success in stroke rehabilitation and its increased risk in stroke patients. Reduced exercise capacity after stroke decreases patients' functionality and further increases the risk of CVD. Carefully selected cardiopulmonary exercise testing (CPET) can be safely used to determine the risk of CVD and to prescribe exercise program in stroke rehabilitation. Objectives: The primary purpose of this study is to determine the most appropriate CPET in patients with stroke. The secondary aim is to determine the relationship between cardiorespiratory fitness and functional status of the patients. Methods: Two CPETs using treadmill and bicycle ergometer protocols determined with a preliminary study were performed on participants. The main outcome measure was VO2peak . Patients were also evaluated according to Brunnstrom motor staging, Modified Ashworth Scale, Berg Balance Scale, and Functional Independence Measure. Results: In total, 38 patients reached higher VO2peak values at treadmill test compared to bicycle test ( p < 0.001). The mean VO2 peak reached at treadmill CPET was 62% of the control group where mean VO2peak reached at bicycle was 76% of the control group. No significant correlation was found between Brunnstrom staging, spasticity, Berg Balance Scale, and VO2peak . Discussion: The results of this study indicate that CPET can be performed safely in stroke patients when appropriate protocol was selected and that treadmill was more appropriate to determine cardiorespiratory fitness in this study population.